Keterlambatan Pengisian PDSS: Menghambat Impian dan Kesempatan Siswa ke Jenjang Pendidikan Tinggi, Mencari Solusi untuk Meningkatkan Efisiensi Guru dalam Era Pendidikan Abad 21 - Benediktus Josua Gea; Zahra Nur Aqilah; Despri Mariyani Siahaan; Herlinda Herlinda; Olivia Hana Putri Nababan; Frita Rohani Manik; Jamaludin Jamaludin (Lembaga Pengembangan Kinerja Dosen, 2025)
Delays in filling in the School and Student Data Base (PDSS) by teachers at several schools in Indonesia, such as SMAN 1 Mempawah and SMK 2 Surakarta, have caused hundreds of students to risk losing the opportunity to take part in the National Achievement Based Selection (SNBP) in 2025. PDSS is an important database containing student and school information, including academic grades and other information required for SNBP. Filling in the PDSS is the responsibility of teachers, especially Dapodik operators and BK counselors, as well as school principals. This delay was caused by negligence in entering data before the specified time limit. As a result, students feel stressed and frustrated because they are threatened with not being able to continue their education to college. The delay in filling out the PDSS reflects a larger problem in the Indonesian education system, where adaptation to technology and development of the skills of teaching staff are urgently needed.